Using Event-Related Potentials to Explore Sentential Code-Switching in English-French Bilinguals - Litcofsky, Kaitlyn (Tufts Archival Research Center, 2005)
Code-switching is known to incur a processing cost, yet little is known regarding what occurs after the code-switched word. The current study tested English (L1)-French (L2) unbalanced bilinguals in an Event-Related Potential (ERP) study in which they read sentences and performed a plausibility judgment. Sentences contained either no code-switches, one code-switch (i.e., switching into the second language), or two code-switches (i.e., switching into the second language and returning to the original language). A Late Positive Component was evoked to L2 items at the code-switched word and an N400 was evoked to all code-switched conditions at the sentence-final word. Results indicate that, for unbalanced bilinguals, it is harder to switch into L2 regardless of the type of code-switch encountered.